Cooling Process of the High-mass Young Stellar Object G24.33+0.14 Following an Accretion Burst - Xiaoyun Xu; Xi Chen; Yang Yang (The Astronomical Journal)
The high-mass young stellar object G24.33+0.14 (G24), has recently been observed to undergo an accretion burst since 2019 September, lasting approximately two years. By utilizing 1.3 mm observational data from the NOrthern Extended Millimeter Array in 2020 March and the Atacama Large Millimeter/submillimeter Array in 2019 September, we have examined the physical environment changes in gas and dust within G24 region during the decay phase of the accretion burst. Following the burst, the continuum emission in the inner core region of G24 diminished by approximately 20%, while the emission in the outer region exhibited an increase by a factor of ∼30%. This pattern indicates that the heat wave, triggered by the accretion burst, radiated outward from the core’s interior to its periphery over the half-year period, with a calculated propagation speed of 0.08–0.38 times the speed of light. Moreover, the methanol emission intensity in this area has experienced a notable decline, with the rate of flux reduction correlating positively with the energy of the upper energy states. This, in conjunction with the analysis of methanol molecular line rotation temperature diagrams for different emitting regions, further substantiates that the core region of G24 cooled down, contrasted with the persistent heating in the outer region following the burst.